Concepts Marketing Mix : Increase in Sales of Airlines Ticket on Route International - Panggabean, Helena Louise; Widiyanto, Prima; Yulihapsari, Ika Utami; Perwitasari, Erni Pratiwi; Maianto, Teguh; Suryawan, Ryan Firdiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to provide an arrangement of literature related to this scientific article by providing an answer. The method used is to describe with qualitative methods the literature review of existing scientific articles and the findings of the results related to this scientific article by corroborating the answers conveyed in the results.Marketing mix has been implemented in the aviation industry, especially in serving passengers and goods that exist today, existing literature that states the findings to strengthen research results in the form of scientific articles can provide a view that the suitability in implementing the marketing mix depends on the existing airlines, because the ability of each management is different to achieve an organizational goal expected by Management over and the expectation of fulfilling passenger expectations. For other researchers in the future to develop using these variables in continuing this research or developing, the results of this collaborative scientific article can add a wealth of literature to aviation bisang in particular